2005
DOI: 10.1097/01.hjr.0000141302.59813.14
|View full text |Cite
|
Sign up to set email alerts
|

Trends in blood lipid levels, blood pressure, alcohol and smoking habits from 1985 to 2002: results from INTERGENE and GOT-MONICA

Abstract: Cardiovascular risk factor patterns change continuously and need to be monitored. The favourable trends in LDL-serum cholesterol and smoking in the Goteborg surveys were paralleled by less favourable trends in being overweight and alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 17 publications
3
29
0
1
Order By: Relevance
“…It has been argued recently that the forces driving these trends operate at the population level rather than the individual level, because the trends occur across the percentile distribution [15,32]; the inter-country evidence we present here further supports that contention. For hypertension, however, the few studies performed report conflicting outcomes [17,21,34].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…It has been argued recently that the forces driving these trends operate at the population level rather than the individual level, because the trends occur across the percentile distribution [15,32]; the inter-country evidence we present here further supports that contention. For hypertension, however, the few studies performed report conflicting outcomes [17,21,34].…”
Section: Discussionsupporting
confidence: 74%
“…The majority of studies have shown a decreasing trend in blood pressure [14,[21][22], although a few studies have detected increasing trends [17][18]20]. Inconsistent trends have also been observed for cholesterol [15][16][17][18]22] and triglycerides [15,20]. Smoking, not a risk factor for metabolic syndrome but a major one for cardiovascular disease and cancer, has decreased especially in men in all western industrialized countries [15,21].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The effect of alcohol consumption on plasma lipid levels and their effects on cardiovascular death have been studied extensively [54]. Ruixing et al reported that the prevalence of hyperlipidemia was positively correlated with alcohol consumption [48].…”
Section: Discussionmentioning
confidence: 99%